PERAN SEMANGAT KERJA DAN KEPUASAN KERJA DALAM MENINGKATKAN PRODUKTIVITAS KERJA - Nurul Ilham; Prasetyo Kurniawan (Al-Ihtiram: Multidisciplinary Journal of Counseling and Social Research, 2026)
This study aims to analyze the role of work spirit and job satisfaction, both partially and simultaneously, on employee work productivity at PT Securindo Packatama Indonesia, South Jakarta Branch, using an associative approach through observation and questionnaire distribution. The results show that work spirit has a positive effect on productivity, as employees with high enthusiasm, motivation, and work energy tend to perform more effectively and achieve optimal results. Job satisfaction also contributes positively, where employees’ satisfaction with their work, work environment, and the rewards they receive is able to enhance commitment and seriousness in carrying out their duties. Simultaneously, both variables become important factors that mutually reinforce each other in encouraging increased work productivity. These findings confirm that the company’s success in improving productivity is strongly influenced by employees’ psychological conditions, particularly their work spirit and level of job satisfaction.